Why do People have the Saving Behavior? A Reference from Sylhet City - Ahsan, Mohammad Kamrul (ABC Journal of Advanced Research, 2016)
Saving is the difference in individual’s disposable earnings and its consumption. Saving is the human behavior. The main aim of this paper is to identify out why people have the saving behavior. A structured questionnaire was used to collect primary data from 232 people from the different parts of Sylhet city in Bangladesh. Several statistical tools, i.e., Descriptive Statistics, Factors Analysis and Multiple Regression Analysis, have been conducted to find out core cause of the human saving behavior. The researcher has found five core factors for having this human saving behavior, i.e., 1. Have a facility in old age, 2. Have enough social security, 3. Purchase land/house, 4.Dependent persons, and 5. Good profit/interest.